2003
DOI: 10.1515/jpm.2003.033
|View full text |Cite
|
Sign up to set email alerts
|

Triplets and quadruplets in Switzerland: comparison with singletons, and evolution over the last decade

Abstract: The incidence of higher-order multiple births in Switzerland dropped for quadruplets in the last decade but has increased for triplets. The mortality and morbidity of triplets is comparable to that of singletons with a similar gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
6

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
2
13
0
6
Order By: Relevance
“…Compared with mothers of twins, mothers of triplets and quadruplets were more likely to be diagnosed with preterm premature rupture of membranes, have excessive bleeding, delivered at less than 29 weeks of gestation, and to have one or more infants die [8]. The gestational age at delivery for quadruplets varied in different reports, ranging from 28 weeks to 31 weeks [1, 2]. Few reports claimed 34 weeks as the gestational age at which delivery took place [9, 10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with mothers of twins, mothers of triplets and quadruplets were more likely to be diagnosed with preterm premature rupture of membranes, have excessive bleeding, delivered at less than 29 weeks of gestation, and to have one or more infants die [8]. The gestational age at delivery for quadruplets varied in different reports, ranging from 28 weeks to 31 weeks [1, 2]. Few reports claimed 34 weeks as the gestational age at which delivery took place [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…The review also showed that respiratory distress syndrome (RDS) was the major morbidity as it was diagnosed in 52% of triplets and 81% of quadruplets [1]. Others have reported similar trends of outcome with RDS occurring in up to 23% of triplets and 65% of quadruplets [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La incidencia natural del embarazo triple varía según factores genéticos y geográficos entre 1 en 3.247 a 1 en 9.828 embarazos (1)(2)(3)(4)(5). En 1958, Geza Kart escribe como introducción para un artí-culo sobre 21 casos: "Por la rareza de los nacimientos triples, la atracción humana por tal suceso es mayor que su importancia práctica".…”
Section: Introductionunclassified